1995
DOI: 10.1007/bf01447091
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and cognitive flexibility: Dissociated dose effects in hyperactive children

Abstract: A randomized, double-blind, placebo-controlled trial was conducted to assess the acute effects of placebo and three doses of methylphenidate (MPH) (0.3, 0.6, O. 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
127
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(140 citation statements)
references
References 54 publications
9
127
4
Order By: Relevance
“…However, the behavioral and cognitive mechanisms of control display different dose-response functions. Dose-related improvements in response inhibition are characterized by an inverted U-shape function, whereas effects on response activation reveal linear dose-response curves (e.g., Tannock et al, 1995). Such observations, along with the present findings, challenge the assumption that stimulants have a unitary mechanism of action that results in a uniform facilitation of performance independent of behavioral and cognitive domains (e.g., response inhibition, memory, etc.).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, the behavioral and cognitive mechanisms of control display different dose-response functions. Dose-related improvements in response inhibition are characterized by an inverted U-shape function, whereas effects on response activation reveal linear dose-response curves (e.g., Tannock et al, 1995). Such observations, along with the present findings, challenge the assumption that stimulants have a unitary mechanism of action that results in a uniform facilitation of performance independent of behavioral and cognitive domains (e.g., response inhibition, memory, etc.).…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the presence of these slopes provides verification that subjects understood the task requirements and followed instructions. In studies of other populations, such as young children, task performance can be affected by inattention and by random response strategies, owing to a lack of motivation or interest on the part of the subject (e.g., Schachar et al, 1995;Tannock et al, 1995). Such response styles are detected by the slope function.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using the stop-signal reaction time task to measure impulsivity have also found baseline dependent effects of amphetamine and methylphenidate on impulsivity [24,25,28]. Further, in humans, individuals with high baseline levels of impulsivity, such as those with attention deficit/hyperactivity disorder (ADHD), show stimulant-induced decreases in impulsivity [69,84,85], further illustrating the importance of preexisting differences in impulsivity on the subsequent effects of stimulant drugs.…”
Section: Discussionmentioning
confidence: 93%
“…The stop signal task in which the subject is required to stop an ongoing behavior in response to a signal has been shown to be relatively specific to ADHD and to improve with stimulant treatment (Tannock et al, 1995b). The task is considered to activate prefrontal cortex (PFC) and basal ganglia.…”
Section: Comorbidity and Adhdmentioning
confidence: 99%